Hey there!!
Recursive formula :
... a( n ) = a ( n - 1 ) + 7
The first term is 12
To find the second term, we will need to substitute 2 in place of ' n '
2 term :
... a( 2 ) = a ( 2 - 1 ) + 7
... a( 2 ) = a( 1 ) + 7
We know a( 1 ) = 12
... a( 2 ) = 12 + 7
... 19 is the second term and we will need to use this to find the other terms.
Hope my answer helps!
Answer:
or
Step-by-step explanation:
Add the exponent two to both sides. After adding -2 and 2 you get 0 and any number raised to the zero power is one. And 4 plus two is 6
=
(X+4)(X-4) is the LCD because you just have to look at the denominators and see what factors or values are not already part of your LCD.
Answer:
no.
Step-by-step explanation:
Answer:
7 notepads
Step-by-step explanation:
5 + 3x = 26
Subtract constant (5)
3x = 21
Divide by coefficient (3)
x=7